Analisis Implementasi Sistem Manajemen Pembelajaran Berbasis Teknologi: Peran Tingkat Keterampilan Teknologi Mahasiswa dalam Peningkatan Keterlibatan dalam Pembelajaran di Perguruan Tinggi - Faisol, Faisol; Astuti, Puji (Efektor, 2024)
The study aims to explore the role of student technology skills levels in the context of the use of learning platforms such as Blackboard Learn, Canvas, and Google Classroom, as well as their relationship with student participatory involvement levels. The research method uses a quantitative approach through surveys of students at various colleges. Using survey data from 120 students, the data was analyzed using regression analysis with the help of the PLS-SEM application, i.e. to understand whether the level of student technology skills mediates the relationship between the use of online learning platforms and student participation rates. The results showed that students' technology skills level played an important role in mediating the relationship between the use of Blackboard Learn, Canvas, and Google Classroom learning platforms and student engagement levels. Students with a higher level of technology skills tend to be more effective in using the Blackboard Learn, Canvas, and Google Classroom platforms that ultimately increase their involvement in the learning process. Knowing the relationship between technology skills, the use of online learning platforms, and the level of student participatory involvement, educational institutions can take concrete steps to increase student engagement in online learning. These can include additional technology skills training, improved accessibility to the learning platform, or the development of more interesting and interactive learning content.